Transfection of Leishmania enriettii and expression of chloramphenicol acetyltransferase gene. - Laban, A (1989)
We report a transient expression transfection system in Leishmania enriettii. A hybrid gene containing an intergenic region of the alpha-tubulin cluster and the bacterial chloramphenicol acetyltransferase (CAT; EC 2.3.1.28) gene is expressed after transfection of L. enriettii with the hybrid plasmid. The expression of the CAT gene is dependent on the presence of sequences from the alpha-tubulin gene. The hybrid gene is also active in Leishmania braziliensis and Leishmania major.